Health beliefs regarding diet: a perspective of hypertensive black individuals - Pires, Cláudia Geovana da Silva; Mussi, Fernanda Carneiro (Revista da Escola de Enfermagem da USP, 2012)
The objective of this descriptive-exploratory study was to identify the health beliefs of black individuals with hypertension regarding the barriers and benefits of diet for controlling the disease, including the sociodemographic factors associated with the health beliefs surrounding diet control. One hundred and six black adults with hypertension were interviewed using a specific instrument. The data were analyzed considering the percentages, frequency of the cases, scores and prevalence ratio. The global analysis of beliefs showed a preponderance of beliefs regarding the benefits of diet control. It was observed that men, younger individuals, lack of a partner and low educational level and income were related to the beliefs regarding the benefits of adopting a healthy diet. In conclusion, health promotion among the black population requires an interdisciplinary approach and specific health policies addressing this populations' needs, aimed at preventive and curative aspects.